2019
DOI: 10.1111/bjh.15802
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of venetoclax monotherapy in patients with relapsed chronic lymphocytic leukaemia in the post‐BCRinhibitor setting: aUKwide analysis

Abstract: Summary Venetoclax is a BCL2 inhibitor with activity in relapsed/refractory (R/R) chronic lymphocytic leukaemia (CLL). We conducted a multi‐centre retrospective analysis of 105 R/R CLL patients who received venetoclax pre‐National Health Service commissioning. The median age was 67 years and median prior lines was 3 (range: 1–15). 48% had TP53 disruption. At ≥2 lines, 60% received a Bruton Tyrosine Kinase inhibitor (BTKi) and no prior phosphoinositide 3‐kinase inhibitor (Pi3Ki), 25% received a Pi3Ki and no pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 21 publications
6
51
0
Order By: Relevance
“…Recent large retrospective, multicentre series (Mato et al, ; Eyre et al, ) have demonstrated reassuringly similar efficacy and survival to trial outcomes. A toxicity analysis [including rates of tumour lysis syndrome (TLS), dose interruptions and discontinuations] has been assessed in a recent all‐age cohort (Roeker et al, ) but the specific question of efficacy and tolerability in elderly non‐trial patients has not been specifically addressed.…”
Section: Treatment Complications Comparing Age Categoriesmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent large retrospective, multicentre series (Mato et al, ; Eyre et al, ) have demonstrated reassuringly similar efficacy and survival to trial outcomes. A toxicity analysis [including rates of tumour lysis syndrome (TLS), dose interruptions and discontinuations] has been assessed in a recent all‐age cohort (Roeker et al, ) but the specific question of efficacy and tolerability in elderly non‐trial patients has not been specifically addressed.…”
Section: Treatment Complications Comparing Age Categoriesmentioning
confidence: 91%
“…Recent large retrospective, multicentre series (Mato et al, 2018b;Eyre et al, 2019) interruptions and discontinuations] has been assessed in a recent all-age cohort (Roeker et al, 2019) but the specific question of efficacy and tolerability in elderly non-trial patients has not been specifically addressed.…”
mentioning
confidence: 99%
“…Also, 29% of patients stopped the venetoclax therapy in the USA study (Mato et al , ) compared to only 8% in the study reported by Eyre et al (). Perhaps the lessons learned from the real‐world ibrutinib experience by UK clinicians led to the very impressive venetoclax results reported in this issue (Eyre et al , )?…”
mentioning
confidence: 85%
“…A similar real-world study from the USA revealed a rather disappointing ORR of 72% but follow-up was very short at only 7 months and results may improve (Mato et al, 2018). Also, 29% of patients stopped the venetoclax therapy in the USA study (Mato et al, 2018) compared to only 8% in the study reported by Eyre et al (2019). Perhaps the lessons learned from the real-world ibrutinib experience by UK clinicians led to the very impressive venetoclax results reported in this issue (Eyre et al, 2019)?…”
mentioning
confidence: 97%
See 1 more Smart Citation